La caución en el juicio de recusación y su vulneración a los derechos constitucionales de: acceso a la justicia, gratuidad de justicia y tutela judicial efectiva - Flores Garzón, Jovi Steeve (2019)
In the code of Civil procedure there was a figure called the challenge with which the plaintiffs could exclude the judges of the processes as long as they were immersed in the grounds to be able to raise the judgement of challenge. In order to bring this trial there was a minimum value which the plaintiff had to pay to challenge a judge, therefore, being a laughable value was not considered as a problem for the plaintiffs. The fundamental problem was for the Judicial function because there was no impediment to the interposition of this trial lawyers abused this legal figure so there was more than two challenges in the same trial, although the legal rule prevented it ), causing the congestion of the judicial apparatus……..